The Global Trends in the Alternative Energetics and Improvement of the State Policy in the Sphere of Fiscal Security: in Search for Equilibrium and Markets - Hnedina Kateryna V.; Petrakov Iaroslav V.; Syzonenko Olena V. (Bìznes Inform, 2017)
Alternative energetics is an important component of the competitiveness and security of the national economy. Its rapid development over the past 10 years is caused by both the attempts of individual countries to maintain and strengthen their competitive advantage in the world markets and the efforts of international organizations (UN, IRENA, IEA) to consolidate different stakeholders to achieve energy and fiscal security, protection of environment and improvement of climate conditions. The article is aimed at generalizing global trends in alternative energetics in the context of development of the State policy in the sphere of fiscal security. A brief overview of the latest trends in the alternative energetics development, most of which focus on identifying the basic sectoral trends, has been provided. However, the issues of fiscal security in the energy sector remain poorly researched, especially in terms of formation of the State policy, consolidating interests of different groups of stakeholders. It has been determined that in the developed countries a significant growth of alternative energetics is caused by the consistent State policy on creation of conditions for formation of effective branch markets and the solving of so-called energy trilemma.